A new species of Philocheras (Decapoda: Caridea: Crangonidae) from Western Australia, with a key to all species of this genus worldwide - Han, Qingxi; Keesing, John K. (Zootaxa, 2018)
One new species and three new distribution records for the family Crangonidae (Crustacea: Decapoda) are reported from Western Australia. A new species, Philocheras gardenensis sp. nov. is described and illustrated based on specimens collected from the Western Australia. The new species closely resembles Philocheras fasciatus (Risso, 1816), but can be distinguished easily by the absence of lobe-like folds on either side of the middle line of the carapace, the presence of a lateral carina extending from the branchiostegal spine, the longer middorsal carina and distolateral tooth of the antennal scale. A key for the genus Philocheras is provided, including currently, a total of 58 species and subspecies reported worldwide. Range extensions of three Crangonid shrimps are reported within Australia, and they are Philocheras obliquus (Fulton & Grant, 1902), Pontocaris arafurae (Bruce, 1988) and Vercoia gibbosa Baker, 1904.